Pengaruh Topografi terhadap Keanekaragaman Gulma dalam Budidaya Talas Beneng (Xanthosoma undipes) - Sofwan Hamid; Nuniek Hermita; Dewi Firnia; Alfu Laila (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Research on weed diversity in talas beneng cultivation areas at various altitudes in Banten is important for providing initial data for weed management. Weed diversity is influenced by internal factors, such as adaptation mechanisms and reproduction, as well as external factors, including environmental conditions, temperature, soil fertility, and altitude. This study was conducted from August to September 2024, observing weed diversity in lowland (343 m a.s.l., Desa Talaga Warna, Serang), midland (615 m a.s.l., Desa Cinyurup, Pandeglang), and highland (761 m a.s.l., Desa Kaduengang, Pandeglang) areas. Sampling involved three plots for each topography, using a purposive sampling method. Field observations were conducted using various weed identification tools, including the PictureThis and Google Lens applications. Data analysis focused on Absolute and Relative Density, Frequency, Dominance, Importance Value Index (IVI), Summed Dominance Ratio (SDR), and Diversity Index. Results indicated that Synedrella nodifora had the highest density in the lowlands, Ageratum conyzoides in the midlands, and Vandellia diffusa in the highlands. The Shannon Diversity Index (H') showed diversity levels of 0.88 (lowland), 1.89 (midland), and 2.68 (highland). These findings suggest that altitude influences weed diversity, with higher elevations supporting greater diversity due to climate and environmental variations. This study highlights the impact of topography on weed communities, providing insights for more targeted weed management in talas beneng cultivation.